High-Throughput Sequencing of Plasma Free DNA In the Second Trimester for Non-Invasive Prenatal Testing of 21-Trisomy Syndrome. (October 2019) - Fu, Xiao; Li, Mu; Wen, Ping
Abstract: Objective: To investigate the application of fetal free DNA (cff DNA) in the peripheral blood of pregnant women to the diagnosis of non-invasive prenatal bowel syndrome (21-trisomy). Methods: 1735 cases of single-pregnant pregnant women with 12-24 weeks of pregnancy were collected, and peripheral blood DNA was extracted. The new generation high-throughput sequencing technology was used for detection and bioinformatics analysis, and amniotic fluid or umbilical cord was selected for 21-three high-risk pregnant women. Blood karyotype analysis was performed. Result: In the 1735 specimens, 12 cases of 21-trisomy positive samples were detected by the new non-invasive prenatal technique, and 12 cases were confirmed by karyotype analysis. The sensitivity and specificity of the non-invasive prenatal technique for the 21-trisomy detection were 100%. Conclusion: The clinical non-invasive prenatal 21-trisomy diagnosis of cffDNA has broad application prospects in prenatal screening.